(untitled) - Louw, Carli

Diamond based electrodes for water quality applications: disinfection, micropollutant removal and the suppression of biofilm proliferation. (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.